Kajian Literasi Media Digital Library Universitas Brawijaya (Studi Kasus pada Mahasiswa Tuna Netra Universitas Brawijaya) - Anita Tri Widiyawati (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The library is the heart of a university that has such extensive benefits. The existence of a library also supports the continuation of the Tri Dharma of Higher Education. The influence and utilization of technology (Digital Library), balanced with basic retention in the use of technology, can make it easier for students with disabilities to get information and facilitate communication with others. Therefore, it is important for the environment both the family environment and friendly environment to introduce the use and use of electronic goods. Through this research, it is known the Digital Library media literacy study on Universitas Brawijaya Blind Students. This study aims to analyze the media literacy of the blind for the Digital Library of Universitas Brawijaya and to find out the supporting factors and factors that inhibit the mastery of media literacy for the blind to the Digital Library of Universitas Brawijaya. This study uses a type of case study research with a qualitative approach while data collection in this study uses qualitative observation techniques, qualitative interviews, reviews information obtained through documents, audio-visual material, and documentation results during the research process.